2022
DOI: 10.3390/life12081143
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy Comprising Paclitaxel and 5-Fluorouracil by Using Folic Acid Functionalized Bovine Milk Exosomes Improves the Therapeutic Efficacy against Breast Cancer

Abstract: Paclitaxel (PAC) has been approved by FDA for clinical use (Taxol®), yet dose-dependent severe toxicity due to the adjuvant Cremophor EL® in combination with ethanol is a major drawback. The drawbacks of the current therapy can be overcome by (i) finding a suitable vehicle that cannot only bypass the above adjuvant but also be used to deliver drugs orally and (ii) combining the PAC with some other chemotherapeutics to have the enhanced therapeutic efficacy. In the current work, we have used folic acid (FA) fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 63 publications
2
33
0
Order By: Relevance
“…For evaluation of their cellular uptake, the isolated exosomes were fluorescently labeled using coumarin-6 as a lipophilic florescent dye (Liang et al., 2021 ; Kumar et al., 2022 ). In brief, equal volumes of exosomal dispersion in PBS and ethanolic dye solution (250 µg/mL) were incubated at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…For evaluation of their cellular uptake, the isolated exosomes were fluorescently labeled using coumarin-6 as a lipophilic florescent dye (Liang et al., 2021 ; Kumar et al., 2022 ). In brief, equal volumes of exosomal dispersion in PBS and ethanolic dye solution (250 µg/mL) were incubated at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…They are basically generated by two invaginations of the plasma membrane. Exosomes are comprised of various surface proteins that are specific to the endosomal pathway, and can enclose nucleic acid, receptors, cytosolic proteins, and drugs [ 96 , 97 ]. The lipidic layer of exosomes varies from other types of extracellular vesicles such as apoptotic bodies and microvesicles as they are enriched in cholesterol and diacylglycerol [ 45 , 98 ].…”
Section: Lipid-based Nanoparticles: a Versatile Drug Delivery Systemmentioning
confidence: 99%
“…It was observed that developed exosomes showed an average particle size of 80–100 nm, with 82% entrapment efficiency. Moreover, the surface functionalized loaded exosomes showed increased cellular uptake and higher apoptotic index, compared to free drugs [ 97 ].…”
Section: Lipid-based Nanoparticles: a Versatile Drug Delivery Systemmentioning
confidence: 99%
“…Biomimetic tumor-derived exosomes loaded with (TEX)-Liposome-paclitaxel (PTX) Microtubule [228] Folic acid (FA)-functionalized bovine milk-derived ssEVs loaded with Paclitaxel (PAC) and 5-fluorouracil (5-FU) Microtubule/synthesis of DNA [229] miR-567 Cancer-associated ATG5 [230] let-7a miRNA EGFR [231] Ultrasonic sensitizer indocyanine green (ICG) Folic acid [232] Deintegrin and metalloproteinase 15 (A15), doxorubicin (Dox) and cholesterol-modified miRNA 159 DNA/GAMYB [233] Cationic bovine serum albumin (CBSA) conjugated siS100A4 nanoparticles Lung PMN [234] Surface display monoclonal antibodies against human CD3 and human HER2 Human CD3 and human HER2 [235] The conjugates of reactive oxygen species (ROS)-responsive sulfide-linked paclitaxel-Linoleic acid conjugates (PTXS-LA) and cucurbitin B (CuB) (EMPC) loaded with CD44…”
Section: Cell Cycle Quiescence and Chemotherapy-resistant Mesenchymal...mentioning
confidence: 99%